2015
DOI: 10.1038/emm.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

MyD88–BLT2-dependent cascade contributes to LPS-induced interleukin-6 production in mouse macrophage

Abstract: Endotoxic responses to bacterial lipopolysaccharide (LPS) are triggered by Toll-like receptor 4 (TLR4) and involve the production of inflammatory mediators, including interleukin-6 (IL-6), by macrophages. The detailed mechanism of IL-6 production by macrophages in response to LPS has remained unclear, however. We now show that LPS induces IL-6 synthesis in mouse peritoneal macrophages via the leukotriene B 4 receptor BLT2. Our results suggest that TLR4-MyD88 signaling functions upstream of BLT2 and that the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 36 publications
2
33
1
Order By: Relevance
“…Although expression of NOX1 in RAW264.7 and peritoneal macrophages was reported previously (Yeligar et al, 2012;Lee et al, 2015), we confirmed the coding sequence of NOX1 mRNA expressed in RAW264.7 to be identical to that of the mouse NOX1 gene. Accordingly, NOX1, ubiquitously expressed in macrophages, may regulate inflammatory responses during TNBS-induced colitis.…”
Section: Nox1 In Colonic Inflammationsupporting
confidence: 86%
See 2 more Smart Citations
“…Although expression of NOX1 in RAW264.7 and peritoneal macrophages was reported previously (Yeligar et al, 2012;Lee et al, 2015), we confirmed the coding sequence of NOX1 mRNA expressed in RAW264.7 to be identical to that of the mouse NOX1 gene. Accordingly, NOX1, ubiquitously expressed in macrophages, may regulate inflammatory responses during TNBS-induced colitis.…”
Section: Nox1 In Colonic Inflammationsupporting
confidence: 86%
“…Indeed, it was reported that NOX1-derived ROSs modulate MAP kinase (Lassegue et al, 2001;Kim et al, 2007) and NF-kB (San Martin et al, 2007;Lee et al, 2015), leading to the induction of various inflammatory mediators. Activation of these redoxdependent pathways downstream of NOX1/NADPH oxidase may elicit the production of inflammatory mediators during TNBS-induced colitis.…”
Section: Nox1 In Colonic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…5C and E). Furthermore, LPS induced NF-κB activation through ROS 41, 42 , MAPKs 42 and PI3-kinase 43 , but inhibitors of ROS (Fig. 6B), MAPKs (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Alam et al have shown that NAC-induced alteration of redox state affects IL-12 production in macrophages both positively and negatively through calmodulin and c-Rel [24]. Another group has reported that NAC treatment inhibits LPS-induced IL-6 production [25], and that IL-10 reciprocally suppresses IL-12 production in mouse macrophages [26]. The latter result would be consistent with our finding that EGT enhances expression of IL-12 while IL-10 is reduced in response to TLR stimulation.…”
Section: Discussionmentioning
confidence: 99%